Bioactive ZnO‐assisted 1393 glass scaffold promotes osteogenic differentiation: Some studies. Issue 5 (30th December 2022) - Ali, Akher; Paladhi, Ankush; Hira, Sumit Kumar; Singh, Bhisham Narayan; Pyare, Ram
Abstract: We developed ZnO‐assisted 1393 bioactive glass‐based scaffold with suitable mechanical properties through foam replica technique and observed to be suitable for bone tissue engineering application. However, the developed scaffolds' ability to facilitate cellular infiltration and integration was further assessed through in vivo studies in suitable animal model. Herein, the pure 1393 bioactive glass (BG) and ZnO‐assisted 1393 bioactive glass‐ (ZnBGs; 1, 2, 4 mol% ZnO substitution for SiO2 in pure BG is named as Z1BG, Z2BG, Z3BG, respectively) based scaffolds were prepared through sol–gel route, followed by foam replica techniques and characterized by a series of in vitro and some in vivo tests. Different cell lines like normal mouse embryonic cells (NIH/3T3), mouse bone marrow stromal cells (mBMSc), peripheral blood mononuclear cells, that is, lymphocytes and monocytes (PBMC) and U2OS (carcinogenic human osteosarcoma cells) were used in determination and comparative analysis of the biological compatibility of the BG and ZnBGs. Also, the alkaline phosphatase (ALP) activity, and osteogenic gene expression by primer‐specific osteopontin (OPN), osteocalcin (OCN), and glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) genes were performed to study osteogenic differentiability of the stromal cells in different BGs. Moreover, radiological and histopathological tests were performed in bone defect model of Wister rats to evaluate the in vivo bone regeneration and healing. Interestingly, these studies demonstrate augmented biological compatibility, and superior osteogenic differentiation in ZnBGs, in particular Z3BG than the pure BG in most cases. Abstract : A total of 1393 glass‐derived scaffolds (BG and ZnBGs) prepared through sol–gel route were characterized for bone formation in vitro and in vivo. The BMSC showed enhanced osteogenesis in Z3BG than BG and Control.